Frequency up-conversion for vibration energy harvesting: a review - Li, Xin (2022)
A considerable amount of ambient vibration energy spreads over an ultra-low frequency spectrum. However, conventional resonant-type linear energy harvesters usually operate within high and narrow frequency bands, which cannot match the frequencies of many vibration sources. If the excitation frequency deviates a bit from the natural frequency of an energy harvester, the energy harvesting performance will deteriorate drastically. Because of the ultra-low frequency characteristic, it is challenging to reliably harvest energy from the ambient vibrations. To address this mismatching issue, the ultra-low frequency ambient vibrations are converted into high-frequency oscillations using certain mechanical mechanisms, which are termed frequency up-conversion techniques. This paper reviews the existing approaches that can realize frequency up-conversion for enhancing energy harvesting from low-frequency vibration sources. According to their working mechanisms, the existing methods are classified into three categories: impact-based, plucking-based, and snap-through-based approaches. The working principles of the three approaches are explained in detail. Represen-tative designs from all categories are reviewed. This overview on the state-of-the-art frequency up-conversion technology would guide the better design of future kinetic energy harvesting systems.